Professional development in MOOC: Teachers motivation - Gonçalves, Bruno (2019)
The increase in the number and quality of technologies has imposed on education in general new forms of learning, some with less relevance, but others with recognized results in the educational and scientific community. The Massive Open Online Courses (MOOC)are an example of one of these technologies with recognized results because that seems to contribute to the acquisition and mastery of digital competences in the context of the realization of the teaching-learning process supported by the networks. It is in these networks that all the participants in the educational process interact and collaborate with all, cultivate connections, debate the themes, present their criticisms, update their knowledge, acquire new skills, make decisions, but generically develop as members of a connectivist community. Based on these assumptions, in this research we intend to make a review of the literature to identify the aspects that, in detriment of regular education, to encourage the teachers to adopt the MOOC as technology for their professional development and to carry out the process of teaching and learning. Thus, through an exploratory research, characterized as documentary, we use the main sources of information, in this case scientific articles published on the subject to understand the relevance and contribution of the MOOC in an educational universe supported by technologies. In general, the results, although preliminary because of temporal limitations issues in accompanying the rapid evolution of the scientific production of knowledge, suggest that on the one hand the teachers opt for MOOC education for the ease of distance learning; on the other hand, adopt the MOOCs for the acquisition of digital skills oriented to the new challenges.